Manejo integrado de Phytophthora infestans en el cultivo de tomate (Solanum lycopersicum) en Ecuador - Zamora Vargas, Daniel David (2023)
P. infestans is one of the most aggressive diseases that attacks tomato crops and very aggressively destroys them in a short time, causing enormous economic losses to the country. It is produced by the phytopathogen P. infestans, an oomycete that has become very important due to its devastating effects and the difficulties to achieve its eradication. P. infestans is a disease that can attack at different stages of the crop and spread rapidly when environmental conditions are favourable. This work aims to determine the integrated management of P. infestans in tomato cultivation. The methodology used is based on bibliographical references. Having as a result that Late blight is in its greatest development when humidity conditions coincide with temperatures for prolonged periods, in this way it favors the normal development of its bone life cycle, increasing rapidly and causing loss due to the disease and the importance of integrated pest management in sustainable agriculture including crop rotation, the use of resistant varieties and organic fungicides, providing the best control of the disease, and its impact on reducing the incidence of P. infestans and se recommended the application of these agronomic practices for the effective and sustainable control of P. infestans in tomato cultivation in Ecuador.